1994
DOI: 10.1002/mpo.2950220107
|View full text |Cite
|
Sign up to set email alerts
|

A study of children, fathered by men treated for testicular cancer, conceived before, during, and after chemotherapy

Abstract: One hundred fifty children of 113 fathers with testicular tumour treated from 1979 on the National Institute of Oncology, Budapest, were studied. Three groups were formed on the basis of the time of conception; 69 children were born before the illness of the fathers, 40 during the 12 pretreatment months, and 41 during or after combined chemotherapy. One hundred fifty control children underwent tonsillectomy/appendectomy, but were otherwise healthy. They were matched according to age, sex, and place of inhabita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…26 -28 In addition, it has also been shown that patients with cancer both before and after treatment have no higher risk of having children with congenital defects. 15,29,30 Nonetheless, caution is needed; a recent study has shown a fivefold increase of hypospadias among males that were conceived through IVF. 31 Further study of the correlation between congenital defects and ART is still warranted.…”
Section: Discussionmentioning
confidence: 97%
“…26 -28 In addition, it has also been shown that patients with cancer both before and after treatment have no higher risk of having children with congenital defects. 15,29,30 Nonetheless, caution is needed; a recent study has shown a fivefold increase of hypospadias among males that were conceived through IVF. 31 Further study of the correlation between congenital defects and ART is still warranted.…”
Section: Discussionmentioning
confidence: 97%
“…Previously we 17,18 and others 19,20 found no evidence of elevation in the occurrence of congenital abnormalities in the offspring born either before or after the father's diagnosis or treatment. As regards childhood tumors occurring below 18 years of age, only scanty or indirect data exist, [21][22][23] which show generally no increased risk of childhood tumors.…”
Section: Discussionmentioning
confidence: 72%
“…Initially, 344 publications were searched from databases and other resources. After screening potentially eligible studies, 27 studies 13,30,32,33,35,38,39,41,43,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] met the inclusion criteria and full texts were subsequently retrieved. The studies included: three retrospective review studies (11.11%) 38,54,58 ; one prospective study (3.7%), 33 seven cohort studies (25.93%), 13,49,56,57,60,62,64 four questionnaire studies (14.81%), 47,48,50,59 three medical record review studies (11.11%), 32,35,51 seven medical review and questionnaire studies (25.93%), 30,39,52,<...>…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The studies included: three retrospective review studies (11.11%) 38,54,58 ; one prospective study (3.7%), 33 seven cohort studies (25.93%), 13,49,56,57,60,62,64 four questionnaire studies (14.81%), 47,48,50,59 three medical record review studies (11.11%), 32,35,51 seven medical review and questionnaire studies (25.93%), 30,39,52,53,55,61,63 one cross-sectional study (3.7%), 41 and one registry study (3.7%). 43 Most studies were conducted in Europe (n = 15, 55.56%), 13,30,32,38,39,41,43,48,50,[56][57][58][59][60]62 followed by The Americas (n = 8, 29.63%), 33,49,[51][52][53][54]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation